Community Participation in Development in Tegalgondo Village, Karangploso District, Malang Regency - ZIDAN GUPARA RAMDANI, ZIDAN; Dwi Kumalasari, Luluk (Hasanuddin Journal of Sociology (HJS), 2024)
This research is entitled Community Participation in Development in Tegalgondo Village, Karangploso District, Malang Regency. Researchers focused this research on the stages of development. As a form of community participation in Tegalgondo Village, Karangploso District, Malang Regency. The involvement of community participation is very important for the realization of village development results. In research using a qualitative research approach to the type of descriptive research. And determining the subject in this study using a purposive sampling technique. In this study, researchers collected data through interviews, observation and documentation. With the subject of the Tegalgondo village secretary, Named Mrs. Sanik. The theory used in this research is the ladder of participation theory (A Leader of Citizen Participation). The theory belongs to Sherry R. Arnstein. This study divides the stages and forms of participation into several parts. and answer the contents of Arnstein's theory. And in the discussion, two forms of community participation in Tegalgondo were found in development, including material participation and non-material participation and two types of development stages that used community participation, namely, the planning stage and the development implementation stage.